The Armenian-German Artaxata Project: preliminary report on the excavations in Artashat 2019 - Lichtenberger, Achim; Zardaryan, Mkrtich H.; Schreiber, Torben; Hamer, Ute; Orendi, Andrea (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The paper deals with the second campaign of the Armenian-German Artaxata Project undertaken in 2019. The classical city of Artashat-Artaxata was founded in the 2nd century BC as the capital of the Armenian kingdom. The city stretches over the 15 hills of the Khor Virap heights and the adjacent plain in the Ararat valley. The new project, started in 2018, focusses on Hill XIII and the Lower city to the south and the north of it. This area was investigated by magnetic prospections in 2018 and on the basis of its results, in total eleven 5 × 5 m trenches were excavated. On the eastern part of Hill XIII several structures of possibly domestic function were uncovered. They were laid out according to a regular plan and in total three phases could be determined. According to C14 data, the first phase already dates to the 2nd-1st centuries BC while the subsequent two phases continue into the 1st century AD. In the 2019 campaign, the overall layout and exact function of the structures could not be determined and more excavations will be undertaken in the forthcoming years. North and north-west of Hill XIII the foundations of piers of an unfinished Roman aqueduct on arches were excavated. This aqueduct is attributed to the period 114-117 AD when the emperor Trajan in vain tried to establish the Roman province of Armenia with Artaxata being its capital. The excavated aqueduct is a unique architectural structure in Armenia and adjacent regions of the Near East.